2015
DOI: 10.1007/s11434-015-0772-5
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Models Drastically Alter Tumor Growth and the Immune Microenvironment in Hepatocellular Carcinoma

Abstract: Initiation and progression of hepatocellular carcinoma (HCC) is intimately associated with a chronically diseased liver tissue. This diseased liver tissue background is a drastically different microenvironment from the healthy liver, especially with regard to immune cell prevalence and presence of mediators of immune function. To better understand the consequences of liver disease on tumor growth and the interplay with its microenvironment, we utilized two standard methods of fibrosis induction and orthotopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…of transcription 3 and nuclear factor κB, and recruit an increased number of inflammatory cells, including neutrophilic granulocytes and mononuclear macrophages, to the lesion site and thereby assist in forming an inflammatory microenvironment (13,30,31). The interaction between tumor cells and inflammatory factors may suppress the immunosurveillance of T and natural killer cells (32), enhance the permeability of blood and lymphatic vessels and degrade the extracellular matrix, thereby potentiating tumor development and metastasis (12,33). Furthermore, tumor cells may secrete inflammatory mediators and thereby assist in forming an inflammatory microenvironment (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of transcription 3 and nuclear factor κB, and recruit an increased number of inflammatory cells, including neutrophilic granulocytes and mononuclear macrophages, to the lesion site and thereby assist in forming an inflammatory microenvironment (13,30,31). The interaction between tumor cells and inflammatory factors may suppress the immunosurveillance of T and natural killer cells (32), enhance the permeability of blood and lymphatic vessels and degrade the extracellular matrix, thereby potentiating tumor development and metastasis (12,33). Furthermore, tumor cells may secrete inflammatory mediators and thereby assist in forming an inflammatory microenvironment (34).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that inflammation is associated with the formation of the tumor microenvironment by inflammatory mediators, including vasoactive amines and cytokines (11)(12)(13). The C-reactive protein (CRP)/albumin (Alb) ratio is used as a novel inflammation-based prognostic indicator in multiple types of tumor.…”
Section: Introductionmentioning
confidence: 99%
“…To do this, we first established a mouse model combining carbon tetrachloride (CCl 4 )-induced liver fibrosis with orthotopic implantation of tumor cells (Fig. 2A and (34)). This model induced robust fibrosis in wild-type (WT) mice, as demonstrated by increases in circulating aminotransferases, hepatic stellate cell activation, and collagen deposition (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2). Induction of inflammatory liver fibrosis enhanced tumor growth, with increased infiltration and altered immune composition in non-tumor liver and tumor compared with tumor engraftment without fibrosis induction (34). IL-18 is produced by many constituents of the tumor microenvironment (25).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation